Effects of Swimming Goggles Wearing on Intraocular Pressure, Ocular Perfusion Pressure, and Ocular Pulse Amplitude. Issue 10 (October 2016) - Paula, Ana P.B.; Paula, Jayter S.; Silva, Marcelo J.L.; Rocha, Eduardo M.; De Moraes, Carlos G.; Rodrigues, Maria L.V.
Abstract : Purpose: To evaluate changes in the ocular pulse amplitude (OPA) and ocular perfusion pressure (OPP), and investigate factors associated with intraocular pressure (IOP) elevation due to periorbital compression during swimming goggles (SG) use. Methods: This cross-sectional study evaluated 35 eyes of 35 healthy volunteers during the wearing of a drilled SG. OPP calculation, Goldman applanation tonometry, and OPA measurements (using Pascal dynamic contour tonometer) were performed before, during, and after SG use. Scleral rigidity (calculated with Schiotz tonometry readings), orbital rim area, exophthalmometry, spherical equivalent, axial length, corneal thickness, and the goggles' rubber elastic force were considered in the multivariable analysis as potentially related to IOP changes. Results: SG significantly increased IOP after 2 minutes of use (13.34±2.67 vs. 23.46±7.20 mm Hg, P <0.0001). After removal, IOP decreased significantly (10.20±5.85 mm Hg, P <0.0001). A inverse correlation between IOP and OPP differences was observed with the SG wearing ( r =−0.57; P =0.0003). Mean OPA was significantly higher during compared with before SG wear (2.57±1.34 vs. 1.82±0.55 mm Hg for the timepoints 2 and 1, respectively; P =0.0064). Only orbital rim area ( P =0.0052) and elastic force ( P =0.0019) were significantly associated with IOP elevation. Conclusions: SG provoked acute IOP elevation and disturbance in the ocular hemodynamics, which was associated with larger orbital rim area and greater SG elastic force. These findings could have implications for subjects at high risk for glaucoma onset or progression.